Avaliação dos níveis plasmáticos de peptídeo natriurético tipo B e relação com obesidade mórbida e comorbidades associadas - Alline Maria Rezende Beleigoli (2010)
Following obesity epidemics, severe obesity has been increasing more importantly than any other form of obesity. Hence, morbid conditions associated to severe obesity, such as heart failure (HF), have had an impressive increase, as well. Diagnosing HF may be challenging, due to unspecific symptoms and signs, and limitations of diagnostic methods. In this context, brain natriuretic peptide (BNP) is a potential tool for identifying HF in the morbid obese population. Following the rules of the Adult Health Sciences Post-Graduation Program of the Medicine School of the Federal University of Minas Gerais, this study was composed by two phases. Each one resulted in a scientific article. The first one is a systematic review, published in Obesity Reviews, in November 2009. The second one is an original article, which displays the results of a cross- sectional study. The systematic review included seventy-five and revealed that natriuretic peptides (NP) have metabolic effects as potent lipolytic agents, in addition to cardiovascular actions. Most of the reviewed articles showed lower NP levels among obese subjects in relation to lean ones. This apparently paradoxical finding points to the potential role of NP in the physiopathological mechanisms of obesity, and obesity associated hypertension and metabolic syndrome. A critical analysis of the selected studies was performed as well. It revealed important heterogeinity among the studies in relation to methodology, participant´s selection criteria and criteria for diagnosing obesity and HF. Hence, definitive conclusions on NP behavior in obesity are not possible and we noticed the necessity for more studies on the subject. The cross-sectional study recruited participants from two obesity clinics in Hospital das Clínicas da UFMG and Centro de Especialidades Médicas da Santa Casa in Belo Horizonte, from July 2008 to July 2009. Its aim was to describe BNP behavior and investigate its utility in predicting ventricular dysfunction in class III obese patients. Clinical, laboratorial, electro and echocardiographic evaluation and BNP measures were performed in eighty-nine participants. BNP values varied from indetectable by the test (< 5.0 pg/mL) to 151.0 pg/mL. Thirty percent of the patients had values below 5.0 pg/mL and only six percent had values on the habitual range considered to diagnose heart failure (= 100 pg/mL). Multivariate ordinal logistic regression analysis verified that left atrial volume (LAV) was the only determinant of BNP levels among all the clinical, laboratorial and echocardiographic data considered relevant to enter the model (p=0.002). LAV is a marker of sustained left ventricular filling pressures and chronic diastolic dysfunction. Based on the systematic review results, it is possible to conclude that NP have important metabolic action as potent lipolytic agents. BNP levels are reduced in the obese subjects in relation to the lean ones. It probably has a role in obesity physiopathology. The second article showed low BNP levels, but the peptide was still able to identify diastolic dysfunction in severe obesity. It was not possible to determine the role of BNP in predicting systolic disfunction in class III obese patients.